IncC conjugative plasmids and SXT/R391 elements repair double-strand breaks caused by CRISPR–Cas during conjugation. Issue 16 (18th June 2020) - Roy, David; Huguet, Kevin T; Grenier, Frédéric; Burrus, Vincent
Abstract: Bacteria have evolved defence mechanisms against bacteriophages. Restriction-modification systems provide innate immunity by degrading invading DNAs that lack proper methylation. CRISPR–Cas systems provide adaptive immunity by sampling the genome of past invaders and cutting the DNA of closely related DNA molecules. These barriers also restrict horizontal gene transfer mediated by conjugative plasmids. IncC conjugative plasmids are important contributors to the global dissemination of multidrug resistance among pathogenic bacteria infecting animals and humans. Here, we show that IncC conjugative plasmids are highly resilient to host defence systems during entry into a new host by conjugation. Using a TnSeq strategy, we uncover a conserved operon containing five genes ( vcrx089 – vcrx093 ) that confer a novel host defence evasion ( hde ) phenotype. We show that vcrx089 – vcrx090 promote resistance against type I restriction-modification, whereas vcrx091–vcxr093 promote CRISPR–Cas evasion by repairing double-strand DNA breaks via recombination between short sequence repeats. vcrx091, vcrx092 and vcrx093 encode a single-strand binding protein, and a single-strand annealing recombinase and double-strand exonuclease related to Redβ and λExo of bacteriophage λ, respectively. Homologous genes of the integrative and conjugative element R391 also provide CRISPR–Cas evasion. Hence, the conserved hde operon considerably broadens the host range of large families of mobile elements spreading multidrug resistance.